The B cell in systemic lupus erythaematosus: a rational target for more effective therapy. Issue 10 (24th August 2007) - Driver, C B; Ishimori, M; Weisman, M H
Abstract : Current treatment options for systemic lupus erythaematosus (SLE) are diverse and poorly defined, and aggressive therapy can be associated with serious toxicity and tolerability issues. There is, therefore, a need for new and improved treatments to be studied thoroughly in well-designed controlled trials. B Cell dysfunction has emerged as a key pathophysiological component of SLE and is a prime target for the development of new agents for a wide range of lupus severity, including advanced disease. Although many current drugs appear to modify B cell function, the advent of new, targeted therapies offers the hope of improved efficacy and a better long-term tolerability profile.